KAJIAN TEKNIS UNEVEN LIGHTING PADA PEMASANGAN PJU - Puji Slamet; Gatut Budiono (Universitas Islam Lamongan, 2023)
The quality of lighting in Public Street Lighting greatly affects the comfort of road users. The unevenness of public street lighting (PJU) which can trigger accidents is influenced by several factors including the width of the road, the height of the poles, the distance between the PJU lamp power poles and the light angle. The width of the road and the height of the poles affect the maximum distance that can be reached by the PJU. The distance between the poles determines the width of the dark position that occurs and the power of the lights. The Uneven Lighting Technical Study on PJU installation in this study was carried out by simulating using PJU S09 RUSH Series lights from the BANDDEL brand with a power of 90 Watt, and the pole height was made variable from 7.5 meters, 8 meters and 9 meters, the distance between the poles was 40 meters and the width walk 6 meters. The results showed that at a pole height of 9 meters, the lighting unevenness occurred at a distance of 18 m from each pole with a lighting intensity value of 7.38 Lux. For a pole height of 8 meters, the lighting unevenness was obtained at a distance of 15 to 18 meters The value of lighting intensity is 6.8 to 7.7 lux from each pole. Whereas at a pole height of 7.5 meters, the light inequality value is obtained at a distance of 15 to 18 meters with a lighting intensity value between 4.68 to 8.09 Lux.